Weaving an Artistic Research Methodology - Dunlop, Jane Frances (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
Weaving occurs as a central theme in my work, as aesthetic motif as well as conceptual frame. In this article, I discuss the “weaving” that forms my approach to artistic research. As artistic research methodology, weaving enacts the generative and relation qualities of feminist epistemologies, through which I locate my own practice, both topically, as a study of emotion and technology, as well as methodologically and politically as invested in feminist approaches to cultural objects and to the knowledge processes that render them meaningful. Through a discussion of my own artistic practice, I demonstrate how weaving operates as an artistic research process that captures the intertwining of academic and creative practice. I argue that it is through the twinned strength and friction of weaving that artistic research creates epistemological possibilities. Weaving is a concept that holds the possibility of multiple threads and thus implies the strength and frictions of things—different contexts, people or concepts—brought together. Weaving is a generative process, a process that creates new totalities through relation while maintaining the discrete identities of the same threads that bind it together.